Melatonin Improves Laying Performance by Enhancing Intestinal Amino Acids Transport in Hens - Liu, Lijuan; Zhang, Siyu; Bao, Jiayang; He, Xiaowen; Tong, Danni; Chen, Cong; Ying, Qingxiang; Zhang, Qing; Zhang, Caiqiao; Li, Jian (Frontiers in Endocrinology, 2018)
The high concentration of melatonin (MEL) in the intestinal mucosa suggests that it has a special physiological function in intestine. In hens, previous studies have shown that MEL treatment promoted egg-laying performance. Considering the importance of amino acids (AA) for egg formation, we hypothesized that MEL may enhance the intestinal absorption of AA from the feed, thus promoting egg laying performance. In this study, we supplemented the hens with MEL for two consecutive weeks. The results showed that, compared with control group, feeding with 0.625 mg MEL/kg diets gave rise to higher egg laying rate (by 4.3%, P = 0.016), increased eggshell thickness (by 16.9%, P < 0.01) and albumen height (by 4.5%, P = 0.042). Meanwhile, feeding with 0.625 and 2.5 mg MEL/kg diets could significantly increase serum levels of aspartic acid, threonine, serine, glutamic acid, glycine, alanine, isoleucine, leucine, tyrosine, phenylalanine, lysine, histidine, arginine and proline. Furthermore, a 0.625 mg MEL/kg diets could significantly increase the expression of PepT1 (by 3949.9%), B0AT (by 6045.9%), b0,+AT (by 603.5%) and EAAT3 (by 412.7%) in the jejunum. Additionally, in the cultured intestinal crypt “organoids”, treatment with 0.5 μM MEL could significantly enhance the expression of PepT1, b0,+AT and EAAT3 mRNAs by 35.4%, 110.0% and 160.1%, respectively. Detection of MEL concentration in serum and intestinal fluid suggested that lower dosage of MEL feeding was mainly acted on intestine locally, and further increased intestinal antioxidases (GPx-3, SOD-1 or PRDX-3) mRNA expression. Taken together, we demonstrated that MEL feeding in laying hens could locally promote the expression and function of AA transporter in small intestine by up-regulating antioxidases expression, and finally elevate laying performance.